Is The Periapical lesion a Risk For Periimplantitis? (A review). - Z Rezaei Esfahrood; M Kadkhodazadeh; R Amid; Ar Rokn (Tehran University of Medical Sciences, 2012)
Conventional implant dentistry has been limited to healed edentulous ridges with adequate bone. Predictable success rates resulted in using dental implants in compromised situations such as insertion into old infected sites or near to pathological areas. There is significant data about marginal bone loss and lack of osseointegration around the neck of implants. However, the data about peri apical implant bone loss is really rare.An electronic search was carried in PubMed regarding articles in the time period from 1980 to 2011. Subsequent manual search was performed included all animal and human case series and clinical trials. Reported success rates and treatment options were calculated in a systematic manner.There is conflicted data showing a relatively accepted success of implantation immediately after removal of infection directly or indirectly in contact with the apical portion of the implants. However, some complications may happen that must be managed.The available data about the periapical implant pathologies is relatively inadequate. However, concluded data represents some clinical comments in order to reduce the complexities.